La motivación del profesor en el proceso de aprendizaje de los niños/as del sexto año de educación básica de la unidad educativa Adolfo Páez del cantón Echeandia, provincia Bolívar en el periodo 2011-2012. - Rochina Rivera, Neli Ines (2012)
If your child behaves as messy, we must believe in their ability to stop and be bringing you our encouragement and confidence in a steady improvement, favoringus so be it. We can say that there is a possibility of solving our problem withthe following points. • Motivate before starting the daily classes. • We give talks reflection. • Have the time needed for classes. • Apply the methodological strategies of motivation. • We must consider the number of students for each classroom. • We have themes that arouse much interest. The motivation is the engine of human behavior, no activities, attitudes, behaviors, skills, abilities, whose origin there is no basic reason, visible, recognizable, to a greater or lesser degree. Motivation is predispose the student to teach what you want, is to take it to actively participate in, work, school, and motivate is to lead the student begin to learn, either by trial and error, imitation or reflection.